2019
DOI: 10.1093/mnras/stz3385
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous detection of an intrinsic absorber and a compact jet emission in the X-ray binary IGR J17091−3624 during a hard accretion state

Abstract: We present a detailed analysis of three XMM-Newton observations of the black hole low-mass X-ray binary IGR J17091-3624 taken during its 2016 outburst. Radio observations obtained with the Australia Telescope Compact Array (ATCA) indicate the presence of a compact jet during all observations. From the best X-ray data fit results we concluded that the observations were taken during a transition from a hard accretion state to a hard-intermediate accretion state. For Observations 1 and 2 a local absorber can be i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…V404 Cyg and IGR J17091-3624) (e.g. Homan et al 2016;Gatuzz et al 2020). Such a persistent existence of optical disk-winds in XRBs even during hard state is in fact consistent with our X-ray wind model; its spectroscopic appearance changes between the two states due to the intrinsic change in an internal physical condition of the wind such as (p, n 17 ) as well as photoionization balance, as found in this work.…”
Section: Summary and Discussionsupporting
confidence: 90%
“…V404 Cyg and IGR J17091-3624) (e.g. Homan et al 2016;Gatuzz et al 2020). Such a persistent existence of optical disk-winds in XRBs even during hard state is in fact consistent with our X-ray wind model; its spectroscopic appearance changes between the two states due to the intrinsic change in an internal physical condition of the wind such as (p, n 17 ) as well as photoionization balance, as found in this work.…”
Section: Summary and Discussionsupporting
confidence: 90%
“…There is evidence for an anticorrelation between jets and disk winds in LMXBs: jets are present in the hard state and disk winds are present in the soft state (e.g., Miller et al 2006bMiller et al , 2008. However, some studies show that jets and disk winds can coexist in the hard state (e.g., Homan et al 2016;Gatuzz et al 2020). Moreover, Homan et al (2016) suggested that disk winds and jets do not need to be mutually exclusive in LMXBs when a source luminosity is higher than a few tens of percent of the Eddington luminosity.…”
Section: Disk Wind In the Hard Intermediate Statementioning
confidence: 99%
“…To study the transition of the source towards quiescence we selected archived Chandra (Weisskopf 1999) and XMM-Newton (Barré, Nye & Janin 1999) observations performed within June -October of 2013. These data, presented here for the first time, correspond to the five last months of the 2011-2013 outburst (for further information about the behaviour of the source in outburst we refer to Gatuzz, et al 2020;Radhika, et al 2018;Xu, et al 2017;Court et al 2017;Grinberg et al 2016 and references therein).…”
Section: Observationsmentioning
confidence: 88%